479 Determining Effects of Residual Feed Intake on Economically Important Production Traits in Crossbreed Beef Cattle. (10th April 2018) - Hershorin, S A; Manjarin, R; Emond, A M; Id-Lahoucine, S; Fonseca, P; Massender, E; Livernois, A; Canovas, A
Abstract: Maximizing feed efficiency will result in lower production costs for raising beef cattle, currently a 70% cost expenditure for the industry. Residual feed intake (RFI) is commonly used as a measure of feed efficiency, and represents the difference between actual and expected feed intakes based on an animal's body weight and growth. Efficient and inefficient animals consume less and more than expected, leading to negative (NEG) and positive (POS) RFI values, respectively. While selecting for RFI can decrease the overall feeding costs, its effect on other production traits remains unknown. The objective of this study aimed to determine the effects of RFI on several production parameters including average daily gain (ADG), tenderness (measured by Warner-Bratzler (WB) shear force of the longissimus dorsi muscle at 7 d post-mortem), marbling score, and scrotal circumference, as a measurement of animal fertility. Data from 2, 578 crossbreed beef cattle was analyzed by a 1–way ANOVA using a linear mixed model that included RFI (POS ≥ 0; NEG < 0) as a fixed effect and age as a covariate. Results were expressed as least square means ± SE. The results show RFI had significant effects on marbling score, which was increased in POS compared to NEG animals (0.034 ± 0.015 vs -0.027 ± 0.016; P < 0.01). RFI did not have significant effects on WB shear force (4.88 ± 0.04 vs 4.93 ± 0.05 kg; P > 0.05), scrotal circumference (5.35 ± 0.60 vs 6.39 ± 0.67 cm; P > 0.05), or ADG (1.70 ± 0.02 vs 1.68 ± 0.03 kg/d; P > 0.05). In conclusion, selection for lower RFI (as part of a multi-trait index selection, among other economically important traits) may not affect beef cattle fertility, but may change muscle marbling with a subsequent effect on meat quality.